Sustainable Decommissioning of Oil Fields and Mines - Environmental Resources Management (World Bank, Washington, DC, 2014)
The overall goal of the decommissioning of oil fields and mines initiative (the 'Initiative') is, in keeping with World Bank policy, to promote sustainable development by assisting governments to undertake and engage in earlier and more systematic, comprehensive, and responsive planning of the decommissioning and closure of mining and oil and gas production operations, as well as more effective implementation. The target audience for this Initiative are the governments of resource-rich countries, specifically the regulatory authorities, institutions, and ministries responsible for: administering mineral resource and oil and gas extraction contracts; issuing environmental permits for exploration, exploitation, and closure; and ensuring that legal, financial and technical measures are in place to address temporary shutdowns as well as complete closure and decommissioning at the end of the productive life of oil and gas and mining operations. This issues paper compiles findings of the first step of the Initiative. It is organized as: section one is an introduction. Section two presents the key trends and challenges faced by both the mining and oil and gas industries in decommissioning operations that have reached the end of their life cycle. Section three organizes findings and issues around what are believed to represent core components of a practical, effective in-country approach to addressing decommissioning and closure needs; and section four identifies next steps.